ASAS KONSELING PRANIKAH ISLAM : PERSPEKTIF ILMU SOSIAL PROFETIK - Muhammad Ali Yunus; Athoillah Islamy (Balai Diklat Keagamaan Papua, 2021)
ABSTRACT This study intends to identify prophetic social values in Islamic premarital counseling principles for family life. This qualitative research is a literature review with a normative philosophical approach. The main data sources of the research used were the book of Bimbingan & Konseling Keluarga Perspektif Islam by Mahmudah and the book Dasar-dasar Konseptual Bimbingan & Konseling Islami by Thohari Musnamar. Meanwhile, secondary data used, namely various relevant scientific studies. The analytical theory used is the Prophetic Social Science paradigm that was initiated by Kuntowijoyo. The nature of this research approach is descriptive-analytic-prescriptive. The results of the study conclude that there are various prophetic social values in the three principles of Islamic premarital counseling. First, the principle of sakinah mawaddah wa rohmah as a humanization value, namely the importance of making the existence of married life a means to manifest various benefits for married life based on the teachings of amar ma'ruf. Second, the principle of communication and deliberation as liberation values, namely the importance of communication and deliberation in addressing problems in order to avoid various family conflicts based on the teachings of nahi munkar (preventing evil). Third, the principles of patience and trustworthiness as transcendence values, namely the importance of transcendent values of Islamic teachings as a paradigmatic basis in addressing problems or needs in family life with an attitude of patience and trust. Keywords : Counseling, Islamic premarital, prophetic social science ABSTRAK Penelitian ini bermaksud untuk mengidentifikasi nilai-nilai sosial profetik dalam asas konseling pranikah Islam bagi kehidupan keluarga. Penelitian kualitatif ini berupa kajian pustaka dengan pendekatan normatif filosofis. Sumber data utama penelitian yang digunakan yakni buku Bimbingan & Konseling Keluarga Perspektif Islam karya Mahmudah dan buku Dasar-dasar Konseptual Bimbingan & Konseling Islami karya Thohari Musnamar. Sementara itu, data sekunder yang digunakan, yakni pelbagai penelitian ilmiah yang relevan. Teori analisis yang digunakan yakni paradigma Ilmu Sosial Profetik yang dicetuskan oleh Kuntowijoyo. Adapun sifat pendekatan penelitian ini, yakni deskriptif-analitik-preskriptif. Hasil penelitian menyimpulkan terdapat berbagai nilai sosial profetik dalam tiga asas konseling pranikah Islam. Pertama, asas sakinah mawaddah wa rohmah sebagai nilai humanisasi, yakni pentingnya menjadikan eksistensi kehidupan pernikahan sebagai sarana untuk mengejawantahkan pelbagai kemaslahatan bagi kehidupan pernikahan berlandaskan pada ajaran amar ma’ruf. Kedua, asas komunikasi dan musyawarah sebagai nilai liberasi, yakni pentingnya komunikasi dan musyawarah dalam menyikapi problem agar dapat menghindarkan pelbagai konflik keluarga dengan melandaskan ajaran nahi munkar (mencegah kemunkaran). Ketiga, asas sabar dan tawakal sebagai nilai transendensi, yakni pentingya nilai-nilai transendensi ajaran Islam sebagai landasan paradigmatik dalam menyikapi persoalan atau kebutuhan dalam kehidupan keluarga dengan sikap sabar dan tawakkal. Kata Kunci : Konseling, pranikah Islam, ilmu sosial profetik